A multifunctional luminescent material based on quinoxaline and triphenylamine groups: polymorphism, mechanochromic luminescence, and applications in high-efficiency fluorescent OLEDs. Issue 9 (3rd February 2022) - Wen, Zhengjie; Yang, Tingting; Zhang, Di; Wang, Zhengqin; Dong, Shufan; Xu, Huixia; Miao, Yanqin; Zhao, Bo; Wang, Hua
Abstract : TQT exhibits multifunctional luminescence characteristics, such as polymorphism and mechanochromic, with potential application in OLEDs. An extremely high photoluminescence quantum yield of 96.5% is achieved in CBP: TQT-G doped film. Abstract : Multifunctional materials with aggregation-induced emission (AIE), mechanochromic luminescence and electroluminescent (EL) features in organic light-emitting devices (OLEDs) are demonstrated to be promising applications in many fields. Herein, we present our work on TQT, using quinoxaline as an acceptor and triphenylamine (TPA) as a donor with a D–A–D symmetrical structure. TQT exhibits high-contrast polymorph-dependent emission, from green to red, and multicolor mechanochromic luminescence (MCL) in aggregate states. Five different crystals (TQT-G = 530 nm, TQT-Y = 575 nm, TQT-Y1 = 584 nm, TQT-O = 593 nm, and TQT-R = 600 nm) were obtained via the slow evaporation of a mixed solution. All crystals and powder phases switch to showing emission at 546 nm after grinding. Among them, TQT-G exhibited remarkable H-aggregate behavior, while TQT-Y tends to form a J-aggregate state. TQT-G and TQT-Y1 have similar configurations and packing models but completely different emission characteristics. A doped device with 20 wt% TQT and a non-doped device showed good electroluminescence performance.